Comprehensive review of macrophage models: primary cells and immortalized lines across species - Ding, Tiansong; Du, Yuhan; Yang, Bin; Tian, Wenfan; Li, Jiapei; Xie, Jinghong (Frontiers in Immunology, 2025)
In order to preserve homeostasis, macrophages—phagocytic innate immune cells—interact with different tissue types, modulating immunological responses and secreting a variety of cytokines. They are extensively dispersed throughout the body’s tissues and organs. Based on their developmental origins, tissue-resident macrophages (TRMs) in humans can be classified into those of embryonic origin and those derived from bone marrow-derived monocytes (BMDMs); embryonically derived macrophages emerge during early development, possess self-renewal capacity, and persist into adulthood in specific tissues such as microglia in the brain and Kupffer cells in the liver, whereas BMDMs originate from hematopoietic stem cells in the bone marrow via monocytic differentiation, infiltrate tissues during inflammation or injury, and differentiate into macrophages that transiently reside in tissues but lack self-renewal capability, thus requiring continuous replenishment. Because of their flexibility and diversity, macrophages participate in a variety of physiological and pathological processes by changing phenotypically and functionally in response to microenvironmental stimuli. This process is known as macrophage polarization. As a consequence, macrophage cultivation in vitro has emerged as a crucial biological technique for mimicking the microenvironment of different disease models. Primary macrophage models and immortalized macrophage models are two distinct types of macrophage models, each with unique origins, functions, benefits, and drawbacks. The features, advantages, disadvantages, isolation procedures, and differentiation induction techniques of primary and immortalized macrophage models are compiled in this review. It also works at the differences between various macrophage cell lines in an effort to shed light on the pathophysiology of inflammatory disorders, viral infection processes, and macrophage immunoregulatory roles.